2010
DOI: 10.4103/0970-4388.73798
|View full text |Cite
|
Sign up to set email alerts
|

Relative position of the mandibular foramen in different age groups of children: A radiographic study

Abstract: The mandible and its growth did not alter the position of the MF, both vertically and horizontally, in relation to different landmarks, and more obtuse GoA indicated an increased growth potential of the mandible. This has major implications in the inferior alveolar nerve block technique when used in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 0 publications
5
23
0
8
Order By: Relevance
“…There have been differing findings in the literature; however, in this study, the mandibular foramen in children between the ages of 5-16 years remained constant in the middle mid-quadrant (M5) (Fig. 1) of the ramus of the mandible in 87.7 % of children, which is in agreement with other researchers (Benham 1976;Hwang et al 1990;Tsai 2004;Ono et al 2005;Ezoddini Ardakani et al 2010;Poonacha et al 2010) on children with Caucasoid and Mongoloid skeletal patterns.…”
Section: Age Groupsupporting
confidence: 94%
See 2 more Smart Citations
“…There have been differing findings in the literature; however, in this study, the mandibular foramen in children between the ages of 5-16 years remained constant in the middle mid-quadrant (M5) (Fig. 1) of the ramus of the mandible in 87.7 % of children, which is in agreement with other researchers (Benham 1976;Hwang et al 1990;Tsai 2004;Ono et al 2005;Ezoddini Ardakani et al 2010;Poonacha et al 2010) on children with Caucasoid and Mongoloid skeletal patterns.…”
Section: Age Groupsupporting
confidence: 94%
“…A summary of the studies available is shown in Table 1. In children of Chinese (Tsai 2004), Brazilian (Kanno et al 2005), Indian (Poonacha et al 2010) and Korean (Kang et al 2013) ethnicity/nationalities, researchers reported that the mandibular foramen was located at the occlusal plane and moved superiorly with increasing age, which supports the current recommendation for the administration of inferior alveolar nerve block (IANB). In younger children, the mandibular foramen was reportedly located below the occlusal plane.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Hetson et al (22) showed it as just posterior to the midpoint of the ramus, which is similar to our results. Poonacha et al (23) showed this location near to the posterior border of the mandible in a group aged between 3 and 13 y. The results of this study and ours seem similar considering the posterior mandibular growth of Poonacha's study group.…”
Section: Discussionsupporting
confidence: 89%
“…It may be possible to reduce IAND after BSSO through a thorough evaluation of MC location and path preoperatively (22,23). A very detailed evaluation of IAN can be made using 3D imaging of MC (14,21).…”
Section: Discussionmentioning
confidence: 99%